Adhesive Film
Patent Information
- Application Number
- JP2023078871
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2023-05-11
- Publication Date
- 2025-01-06
- Estimated Expiration
- 2031-06-10
AI Technical Summary
【0012】 本発明によれば、ペンタフルオロベンゼン骨格を有する、比較的に安価な帯電防止剤を含有させた粘着剤を用いることで、粘着剤の全体コストを抑えることができ、帯電防止性やリワーク性などの欠点などの課題を改善することが可能となる。
Smart Images

Figure 0007608514000001 
Figure 0007608514000002 
Figure 0007608514000003
Abstract
Description
[Technical field]
[0001] The present invention relates to an adhesive composition containing an antistatic agent, and an adhesive film. More specifically, the present invention relates to an adhesive composition containing a compound having a pentafluorophenyl group (C6F5 group) (hereinafter referred to as a "pentafluorobenzene compound") as an antistatic agent, and relates to an adhesive composition having excellent antistatic properties without impairing adhesive performance and also excellent reworkability, and an adhesive film using the same. [Background technology]
[0002] Conventionally, in the manufacturing, processing, and assembly processes of precision parts and components such as electronic device parts, optical device parts, and image display panels, surface protection films have been affixed to the surfaces of these precision parts and components to temporarily protect the surfaces of these precision parts and components and to prevent the adhesion of particle and gaseous contaminants from the working environment and the occurrence of scratches and dents. For example, a surface protection film used in the process of manufacturing optical components such as polarizing plates and retardation plates, which are components that make up liquid crystal displays, has an adhesive layer formed on one side of an optically transparent polyethylene terephthalate (PET) resin film, and a release film that has been treated to release the adhesive layer to protect it until it is attached to the optical component is attached on top of the adhesive layer.
[0003] In addition, optical components such as polarizing plates and retardation plates are subjected to product inspection involving optical evaluation of the display performance, hue, contrast, and inclusion of foreign matter of the liquid crystal display panel with a surface protection film attached, so the required performance of the surface protection film is that the adhesive layer must be free of air bubbles and foreign matter. Moreover, in recent years, when peeling off a surface protection film from an optical component such as a polarizing plate or a retardation plate, there has been concern that peeling charge generated by static electricity generated when the adhesive layer is peeled off from the adherend may affect failure of the electrical control circuit of the liquid crystal display, and therefore there is a demand for adhesive layers with excellent antistatic performance. In addition, when a surface protection film is attached to an optical component such as a polarizing plate or a retardation plate, the surface protection film may be peeled off once and then reattached for various reasons, and in such cases, the surface protection film is required to be easy to peel off from the optical component to which it is attached (reworkability). Thus, in recent years, the required performance of the adhesive layer constituting the surface protection film includes stability of adhesive strength over time, excellent antistatic performance, and rework performance, in order to make the surface protection film easier to use. However, while it is possible to separately satisfy each of the required performance characteristics of the adhesive layer constituting the surface protection film, namely, adhesive strength stability over time, excellent antistatic performance, and rework performance, it has been a difficult task to simultaneously satisfy the required performance characteristics of the adhesive layer of the surface protection film at low cost.
[0004] For example, the following proposals are known regarding the stability of adhesive strength over time. In an acrylic adhesive layer made by crosslinking a copolymer of a (meth)acrylic acid alkyl ester having an alkyl group with 7 or less carbon atoms and a carboxyl group-containing copolymerizable compound with a crosslinking agent as the main component, the adhesive transfers to the adherend when adhered for a long period of time, and the adhesive strength to the adherend increases significantly over time. To avoid this, a known adhesive layer is provided using a copolymer of a (meth)acrylic acid alkyl ester having an alkyl group with 8 to 10 carbon atoms and a copolymerizable compound having an alcoholic hydroxyl group, and crosslinking the copolymer with a crosslinking agent (Patent Document 1). Also proposed is a pressure-sensitive adhesive layer prepared by blending a small amount of a copolymer of an alkyl (meth)acrylate ester and a carboxyl group-containing copolymerizable compound with the above-mentioned copolymer and crosslinking the resulting copolymer with a crosslinking agent.
[0005] Regarding excellent antistatic performance, a method of kneading an antistatic agent into a base film has been disclosed as a method for imparting antistatic properties to a surface protective film. Examples of the antistatic agent disclosed include: (a) various cationic antistatic agents having a cationic group such as a quaternary ammonium salt, a pyridinium salt, or a primary to tertiary amino group; (b) anionic antistatic agents having an anionic group such as a sulfonate group, a sulfate group, a phosphate group, or a phosphonate group; (c) amphoteric antistatic agents such as amino acid-based and amino sulfate-based agents; (d) nonionic antistatic agents such as amino alcohol-based, glycerin-based, and polyethylene glycol-based agents; and (e) polymer-type antistatic agents obtained by increasing the molecular weight of the above-mentioned antistatic agents (Patent Document 2).
[0006] In recent years, it has been proposed to incorporate such antistatic agents into the base film, or to incorporate them directly into the pressure-sensitive adhesive layer rather than coating the surface of the base film (Patent Document 3). Patent Document 3 discloses an antistatic adhesive composition including (1) a copolymer obtained by radiation polymerization of a polymerizable mixture containing as main components (a) a urethane acrylate, (b) a (meth)acrylate having a polyalkylene oxide chain, and (c) an adhesive strength-imparting monomer, and (2) an ionic compound, and an adhesive sheet using the same. A specific method for producing the adhesive composition is described as mixing an ionic compound such as lithium perchlorate with a polymerizable mixture containing a urethane acrylate such as polyester urethane acrylate, a (meth)acrylate monomer having a polyoxyalkylene chain such as methoxypolyethylene glycol acrylate, an adhesive strength-imparting monomer such as hydroxypropyl acrylate, and, if necessary, a further comonomer such as isooctyl acrylate, and adding a photopolymerization initiator if necessary, stirring until completely dissolved, and then curing by irradiating with ultraviolet light or the like to obtain the adhesive composition. However, lithium perchlorate used as the ionic compound is corrosive to metals, and therefore there is a problem in that the locations where the obtained antistatic pressure-sensitive adhesive composition can be used are limited.
[0007] Regarding reworkability, for example, a pressure-sensitive adhesive composition has been proposed in which an isocyanate compound curing agent and a specific silicate oligomer are blended in an acrylic resin in an amount of 0.0001 to 10 parts by weight per 100 parts by weight of the acrylic resin (Patent Document 4). In Patent Document 4, it is described that the main monomer component is an acrylic acid alkyl ester having an alkyl group with about 2 to 12 carbon atoms or a methacrylic acid alkyl ester having an alkyl group with about 4 to 12 carbon atoms, and that it may contain other functional group-containing monomer components such as a carboxyl group-containing monomer. In general, it is preferable to contain 50% by weight or more of the main monomer, and it is desirable that the content of the functional group-containing monomer component is 0.001 to 50% by weight, preferably 0.001 to 25% by weight, and more preferably 0.01 to 25% by weight. The pressure-sensitive adhesive composition described in Patent Document 4 is described as having reworkability because the change in cohesive strength and adhesive strength over time is small even at high temperature or high temperature and high humidity, and it also shows excellent effect in curved surface adhesive strength. In general, when the adhesive layer is made soft, it is easy for adhesive residue to occur and reworkability is easily reduced. In other words, when it is applied incorrectly, it is difficult to peel off and difficult to reapply. For this reason, it is considered necessary to crosslink a monomer having a functional group such as a carboxyl group to the base resin to give the adhesive layer a certain hardness in order to provide reworkability. [Prior art documents] [Patent documents]
[0008] [Patent Document 1] Japanese Patent Application Publication No. 63-225677 [Patent Document 2] Japanese Patent Application Publication No. 11-070629 [Patent Document 3] JP 2000-129235 A [Patent Document 4] Japanese Patent Application Publication No. 8-199130 Summary of the Invention [Problem to be solved by the invention]
[0009] In conventional technology, while it was possible to separately satisfy the required performance of the adhesive layer constituting a surface protection film, namely, adhesive strength stability over time, excellent antistatic performance, and rework performance, it was a difficult task to simultaneously satisfy the required performance required of the adhesive layer of a surface protection film at low cost. The present invention has been made in consideration of the above circumstances, and an object of the present invention is to provide a pressure-sensitive adhesive composition containing an antistatic agent, which has excellent antistatic properties without impairing adhesive performance and also has excellent reworkability, and a pressure-sensitive adhesive film using the same. [Means for solving the problem]
[0010] In order to solve the above problems, the present invention provides a pressure-sensitive adhesive composition comprising an acrylic polymer, a crosslinking agent, and an antistatic agent, the acrylic polymer being a copolymer selected from the following acrylic polymers (1) to (3): Acrylic polymer (1): (A) a copolymer obtained by copolymerizing at least one (meth)acrylic acid ester monomer having an alkyl group with a carbon number of C1 to C14 and (B) at least one copolymerizable vinyl monomer having a hydroxyl group and / or a carboxyl group; Acrylic polymer (2); (A) a copolymer obtained by copolymerizing at least two or more kinds of (meth)acrylic acid ester monomers having an alkyl group with a carbon number of C1 to C14; Acrylic polymer (3); (A) a copolymer obtained by copolymerizing at least one (meth)acrylic acid ester monomer having an alkyl group with a carbon number of C1 to C14 and at least one aromatic monomer; The pressure-sensitive adhesive composition contains, as the crosslinking agent, one or more types selected from the group consisting of difunctional or higher isocyanate compounds, difunctional or higher epoxy compounds, difunctional or higher acrylate compounds, and metal chelate compounds, and the pressure-sensitive adhesive composition contains, as the antistatic agent, an ionic compound in a ratio of 0.1 to 10 parts by weight per 100 parts by weight of the copolymer, the antistatic agent being an ionic compound consisting of an anion having a pentafluorophenyl group (C6F5 group) and a cation, and the cation being one type selected from the group of cations consisting of pyridinium, imidazolium, and pyrrolidinium. The anion of the ionic compound is C6F5COO - , C6F5(CH2) n COO - , C6F5(CF2) n COO - , C6F5O(CH2) n COO - , C6F5(CH=CH) n COO - , C6F5SO3 - , C6F5(CH2) n SO3 - , C6F5(CF2) n SO3 - , C6F5O(CH2) n SO3 - , C6F5(CH=CH) n SO3 - , C6F5O - , C6F5(CH2) n O - , C6F5(CF2) n O - , C6F5O(CH2) n O - , (C6F5)2CHO - , (C6F5)3CO - , (C6F5)4B - , C6F5OSO3 - , C6F5O(CH2) n SO3 - , C6F5O(CF2) n SO3 - , (C6F5CO)2N- , (C6F5CO)3C - , (C6F5SO2)2N - , (C6F5SO2)3C - , (C6F5OSO2)2N - , (C6F5OSO2)3C - , C6F5PO3 2- It is preferable that the anion is one selected from the group consisting of:
[0011] The present invention also provides a pressure-sensitive adhesive film comprising a substrate and a pressure-sensitive adhesive layer formed of the pressure-sensitive adhesive composition laminated on one surface of the substrate. The present invention also provides a surface protection film using the pressure-sensitive adhesive film. The present invention also provides a surface protection film for a polarizing plate, which uses the pressure-sensitive adhesive film. The present invention also provides an optical surface protection film using the pressure-sensitive adhesive film. The present invention also provides an optical film with a pressure-sensitive adhesive, comprising an optical film and a pressure-sensitive adhesive layer made of the pressure-sensitive adhesive composition laminated on at least one surface of the optical film. The present invention also provides the above-described pressure-sensitive adhesive optical film, wherein the optical film is a polarizing plate. The present invention also provides an image display device comprising the above-described pressure-sensitive adhesive optical film laminated via the pressure-sensitive adhesive layer. Effect of the Invention
[0012] According to the present invention, by using an adhesive containing a relatively inexpensive antistatic agent having a pentafluorobenzene skeleton, it is possible to reduce the overall cost of the adhesive and improve issues such as defects in antistatic properties and reworkability. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] The present invention will be described below based on preferred embodiments. The adhesive composition of the present invention comprises an adhesive polymer that is the main component of the adhesive, and an antistatic agent that imparts antistatic performance, and is characterized in that the antistatic agent contains a pentafluorobenzene compound, which is a compound having a pentafluorophenyl group (C6F5 group). This provides excellent antistatic performance and makes it possible to improve issues such as shortcomings in antistatic properties and reworkability.
[0014] The adhesive polymer used in the present invention is preferably an acrylic polymer, and in particular, a copolymer composition containing as a main component at least one kind of (A) alkyl (meth)acrylate monomer having an alkyl group with a carbon number of C1 to C14. (A) Examples of alkyl (meth)acrylate monomers having an alkyl group with a carbon number of C1 to C14 include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, butyl (meth)acrylate, isobutyl (meth)acrylate, pentyl (meth)acrylate, hexyl (meth)acrylate, heptyl (meth)acrylate, octyl (meth)acrylate, isooctyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, nonyl (meth)acrylate, isononyl (meth)acrylate, decyl (meth)acrylate, cyclopentyl (meth)acrylate, cyclohexyl (meth)acrylate, etc. The alkyl group of the alkyl (meth)acrylate monomer may be linear, branched, or cyclic.
[0015] The adhesive polymer used in the present invention may be a copolymer composition consisting of (A) at least one alkyl (meth)acrylate monomer having an alkyl group with a carbon number of C1 to C14 and at least one other copolymerizable monomer. In this case, the other copolymerizable monomer may be (B') a copolymerizable vinyl monomer having a vinyl group or (B) a copolymerizable vinyl monomer containing a hydroxyl group and / or a carboxyl group. Examples of the copolymerizable vinyl monomer containing a hydroxyl group include hydroxyl group-containing (meth)acrylic acid esters such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, and 8-hydroxyoctyl (meth)acrylate; and hydroxyl group-containing (meth)acrylamides such as N-hydroxy(meth)acrylamide, N-hydroxymethyl (meth)acrylamide, and N-hydroxyethyl (meth)acrylamide. It is preferable to use at least one selected from these compound groups. Examples of the copolymerizable vinyl monomer containing a carboxyl group include (meth)acrylic acid, itaconic acid, crotonic acid, maleic acid, fumaric acid, carboxyethyl (meth)acrylate, and carboxypentyl (meth)acrylate, and it is preferable to use at least one selected from this compound group. Examples of copolymerizable vinyl monomers other than those mentioned above include aromatic group-containing (meth)acrylic acid esters such as benzyl (meth)acrylate and phenoxyethyl (meth)acrylate, as well as various vinyl monomers such as styrene, acrylamide, acrylonitrile, methyl vinyl ether, ethyl vinyl ether, vinyl acetate, and vinyl chloride.
[0016] In addition, as the adhesive polymer used in the present invention, a copolymer composition consisting of at least two or more kinds of (A) alkyl (meth)acrylate monomers having a carbon number of C1 to C14 in the alkyl group can be used. In this case, the copolymer composition can be obtained without using a copolymerizable vinyl monomer other than (A) alkyl (meth)acrylate monomer having a carbon number of C1 to C14 in the alkyl group.
[0017] The pressure-sensitive adhesive composition of the present invention contains at least one pentafluorobenzene compound, which is a compound having a pentafluorophenyl group (C6F5 group), as an essential component. The pentafluorobenzene compound is preferably contained as an antistatic agent. The general formula of the pentafluorobenzene compound is shown in the following formula (Chemical Formula 1). In the formula, Y represents a partial structure containing a functional group having antistatic properties, such as an anionic functional group or a nonionic polyether functional group.
[0018] [ka]
[0019] When the pentafluorobenzene compound used in the present invention is nonionic, examples of the polyether functional group include polyalkylene oxide groups such as polyethylene oxide groups and polypropylene oxide groups. Examples of the terminal group of the polyether functional group include a hydrogen atom, an alkyl group, an acyl group, and an amino group.
[0020] The pentafluorobenzene compound used in the present invention is preferably an ionic compound consisting of an anion and a cation, and more preferably, this ionic compound has as an anion one kind selected from a group of anions consisting of various anions having a pentafluorophenyl group (CF group). The anion having a pentafluorophenyl group (C6F5 group) is a carboxylate anion having a C6F5 group (COO - anion containing SO3 - anion containing PO3 2- anions containing O), alkoxides or phenoxy anions containing C6F5 groups (Y is replaced with O - anion containing N) and imide anion having a C6F5 group (Y is replaced with N - anion containing C6F5 group, methide anion (Y is replaced with C -anion containing a C6F5 group, a borate anion (Y is replaced with B - (anions containing Specific examples of anions having a C6F5 group include, but are not limited to, C6F5COO - , C6F5(CH2) n COO - , C6F5(CF2) n COO - , C6F5O(CH2) n COO - , C6F5(CH=CH) n COO - , C6F5SO3 - , C6F5(CH2) n SO3 - , C6F5(CF2) n SO3 - , C6F5O(CH2) n SO3 - , C6F5(CH=CH) n SO3 - , C6F5O - , C6F5(CH2) n O - , C6F5(CF2) n O - , C6F5O(CH2) n O - , (C6F5)2CHO - , (C6F5)3CO - , C6F5OSO3 - , C6F5O(CH2) n SO3 - , C6F5O(CF2) n SO3 - , (C6F5CO)2N - , (C6F5CO)3C - , (C6F5SO2)2N - , (C6F5SO2)3C - , (C6F5OSO2)2N - , (C6F5OSO2)3C - , C6F5PO3 2- , (C6F5)4B - (where n is an integer of 1 or greater). The pentafluorobenzene compound used in the present invention is particularly a pentafluorobenzene carboxylate anion (wherein Y is COO - An anion that is C6F5COO - ), pentafluorobenzenesulfonic acid anion (Y above is SO3 - The anion is C6F5SO3 - ), pentafluorophenoxy anion (where Y is O - An anion that is C6F5O - It is preferable that the compound is an ionic compound containing at least one anion selected from the group consisting of
[0021] The antistatic agent preferably contains 0.1 to 20 parts by weight, more preferably 0.1 to 10 parts by weight, of (C) an ionic compound having one kind selected from the above-mentioned pentafluorobenzene compound group as an anion, relative to 100 parts by weight of the copolymer composition of the adhesive polymer used in the present invention.
[0022] The ionic compound is preferably an ionic compound having, as a cationic component, one type selected from the group consisting of pyridinium, imidazolium, sulfonium, phosphonium, pyrrolidinium, guanidinium, ammonium, isouronium, thiouronium, piperidinium, pyrazolium, morpholinium, and the like. Examples of pyridinium cations include 1-hexyl-4-methylpyridinium cation, 1-octyl-4-methylpyridinium cation, 1-butyl-4-methylpyridinium cation, 2-methyl-1-dodecylpyridinium cation, 1-methylpyridinium cation, 1-ethylpyridinium cation, 1-butylpyridinium cation, 1-hexylpyridinium cation, 1-octylpyridinium cation, 1-nonylpyridinium cation, and 1-dodecylpyridinium cation. Examples of the imidazolium cation include 1,3-dimethylimidazolium cation, 1-ethyl-3-methylimidazolium cation, 1-butyl-3-methylimidazolium cation, 1-octyl-3-methylimidazolium cation, 1-nonyl-3-methylimidazolium cation, and 1-dodecyl-3-methylimidazolium cation. Examples of pyrrolidinium cations include 1-methyl-1-ethylpyrrolidinium cation, 1-methyl-1-butylpyrrolidinium cation, 1-butyl-1-butylpyrrolidinium cation, 1-octyl-1-octylpyrrolidinium cation, 1-butyl-1-octylpyrrolidinium cation, 1-nonyl-1-nonylpyrrolidinium cation, and 1-dodecyl-1-dodecylpyrrolidinium cation. Examples of the ammonium cation include aliphatic ammonium cations such as tetrabutylammonium cation, tetrapentylammonium cation, trioctylmethylammonium cation, trimethylhexylammonium cation, trimethylpropylammonium cation, N,N-dimethyl-N,N-didecylammonium cation, N,N-diallyl-N-hexyl-N-methylammonium cation, and trimethylethylammonium cation; and aromatic ammonium cations such as phenyltrimethylammonium cation, dimethylethylphenylammonium cation, and diethylmethylphenylammonium cation. Examples of the piperidinium cation include 1-methyl-1-ethylpiperidinium cation, 1-methyl-1-butylpiperidinium cation, 1-butyl-1-butylpiperidinium cation, 1-octyl-1-octylpiperidinium cation, and 1-butyl-1-octylpiperidinium cation. Examples of the morpholinium cation include 4-methyl-4-ethylmorpholinium cation, 4-methyl-4-butylmorpholinium cation, 4-methyl-4-hexylmorpholinium cation, 4-octyl-4-octylmorpholinium cation, 4-butyl-4-octylmorpholinium cation, 4-nonyl-4-nonylmorpholinium cation, and 4-dodecyl-4-dodecylmorpholinium cation. Examples of the phosphonium cation include a tetrabutylphosphonium cation, a triisobutylmethylphosphonium cation, a tetrapentylphosphonium cation, and a tetrahexylphosphonium cation.
[0023] Examples of ionic compounds having a pyridinium cation and an anion of a pentafluorobenzene compound include 1-hexyl-4-methylpyridinium pentafluorobenzenecarboxylate, 1-hexyl-4-methylpyridinium pentafluorophenoxy salt, 1-hexyl-4-methylpyridinium pentafluorobenzenesulfonate, 1-octyl-4-methylpyridinium pentafluorobenzenecarboxylate, 1-octyl-4-methylpyridinium pentafluorophenoxy salt, 1-octyl-4-methylpyridinium pentafluorobenzenesulfonate, 1-butyl-4-methylpyridinium pentafluorobenzenecarboxylate, 1-butyl-4-methylpyridinium pentafluorophenoxy salt, 1-butyl-4-methylpyridinium pentafluorobenzenesulfonate, 2-methyl-1-dodecylpyridinium pentafluorobenzenecarboxylate, and 2-methyl-1-dodecylpyridinium. pentafluorophenoxy salt, 2-methyl-1-dodecylpyridinium pentafluorobenzenesulfonate, 1-butylpyridinium pentafluorobenzenecarboxylate, 1-butylpyridinium pentafluorophenoxy salt, 1-butylpyridinium pentafluorobenzenesulfonate, 1-octylpyridinium pentafluorobenzenecarboxylate, 1-octylpyridinium pentafluorophenoxy salt, 1-octylpyridinium pentafluorobenzenesulfonate, 1-nonylpyridinium pentafluorobenzenecarboxylate, 1-nonylpyridinium pentafluorophenoxy salt, 1-nonylpyridinium pentafluorobenzenesulfonate, 1-dodecylpyridinium pentafluorobenzenecarboxylate, 1-dodecylpyridinium pentafluorophenoxy salt, 1-dodecylpyridinium pentafluorobenzenesulfonate, 1-octyl-3,5dimethylpyridinium Examples include pentafluorobenzenecarboxylate, 1-octyl-3,5 dimethylpyridinium pentafluorophenoxy salt, and 1-octyl-3,5 dimethylpyridinium pentafluorobenzenesulfonate. Examples of ionic compounds having an imidazolium cation and an anion of a pentafluorobenzene compound include 1-butyl-3-methylimidazolium pentafluorobenzenecarboxylate, 1-butyl-3-methylimidazolium pentafluorophenoxy salt, 1-butyl-3-methylimidazolium pentafluorobenzenesulfonate, 1-octyl-3-methylimidazolium pentafluorobenzenecarboxylate, 1-octyl-3-methylimidazolium pentafluorophenoxy salt, 1-octyl-3-methylimidazolium pentafluorobenzenesulfonate, 1-nonyl-3-methylimidazolium pentafluorobenzenecarboxylate, 1-nonyl-3-methylimidazolium pentafluorophenoxy salt, 1-nonyl-3-methylimidazolium pentafluorobenzenesulfonate, and 1-dodecyl-3-methylimidazolium Examples of the compound include pentafluorobenzene carboxylate, 1-dodecyl-3-methylimidazolium pentafluorophenoxy salt, and 1-dodecyl-3-methylimidazolium pentafluorobenzenesulfonate. Examples of ionic compounds having a pyrrolidinium cation and an anion of a pentafluorobenzene compound include 1-butyl-1-butylpyrrolidinium pentafluorobenzenecarboxylate, 1-butyl-1-butylpyrrolidinium pentafluorophenoxy salt, 1-butyl-1-butylpyrrolidinium pentafluorobenzenesulfonate, 1-octyl-1-octylpyrrolidinium pentafluorobenzenecarboxylate, 1-octyl-1-octylpyrrolidinium pentafluorophenoxy salt, and 1-octyl-1-octylpyrrolidinium pentafluorobenzenesulfonate.
[0024] The pressure-sensitive adhesive layer made of the pressure-sensitive adhesive composition has a surface resistance of 1.0×10 +12 It is preferably Ω / □ or less. If the surface resistance is high, the performance of dissipating static electricity generated by charging during peeling is poor, so by making the surface resistance sufficiently small, the peeling electrification voltage generated by static electricity generated when the pressure-sensitive adhesive layer is peeled off from the adherend is reduced, and it is possible to suppress the influence on the electrical control circuit etc. of the adherend.
[0025] It is preferable that the adhesive composition of the present invention crosslinks the adhesive polymer when forming the adhesive layer. To crosslink, the adhesive composition may contain a known crosslinking agent, or may be crosslinked by photocrosslinking such as ultraviolet (UV) light. Examples of the crosslinking agent include difunctional or higher isocyanate compounds, difunctional or higher epoxy compounds, difunctional or higher acrylate compounds, and metal chelate compounds. Further, as other components, known additives such as silane coupling agents, antioxidants, surfactants, curing accelerators, plasticizers, fillers, curing retarders, processing aids, and antiaging agents can be appropriately blended in. These can be used alone or in combination of two or more kinds.
[0026] The pressure-sensitive adhesive film of the present invention is a film in which a pressure-sensitive adhesive layer made of the pressure-sensitive adhesive composition of the present invention is laminated on one side of a substrate film. The pressure-sensitive adhesive film of the present invention can be suitably used as a surface protection film, a surface protection film for a polarizing plate, or an optical surface protection film. As the base film of the pressure-sensitive adhesive layer and the release film (separator) that protects the adhesive surface, a resin film such as a polyester film can be used. The substrate film may be subjected to an antifouling treatment using a silicone-based or fluorine-based release agent or coating agent, or silica microparticles or the like, or an antistatic treatment by coating or kneading an antistatic agent, on the side opposite to the side on which the pressure-sensitive adhesive layer of the resin film is formed. The release film is subjected to a release treatment with a silicone-based or fluorine-based release agent on the surface thereof that is to be joined to the adhesive surface of the adhesive layer. In the case of an optical surface protection film such as a surface protection film for a polarizing plate, the base film and the pressure-sensitive adhesive layer preferably have sufficient transparency. EXAMPLES
[0027] The present invention will now be described in detail with reference to examples.
[0028] <Production of Acrylic Copolymer> [Example 1] Nitrogen gas was introduced into a reactor equipped with a stirrer, a thermometer, a reflux condenser, and a nitrogen inlet tube, and the air in the reactor was replaced with nitrogen gas. Then, 100 parts by weight of 2-ethylhexyl acrylate, 1.5 parts by weight of 6-hydroxyhexyl acrylate, and 100 parts by weight of a solvent (ethyl acetate) were added to the reactor. Then, 0.1 parts by weight of azobisisobutyronitrile as a polymerization initiator was dropped over 2 hours, and the mixture was reacted at 65°C for 8 hours to obtain an acrylic copolymer solution 1 of Example 1 having a weight average molecular weight of 500,000. [Examples 2 to 7 and Comparative Examples 1 to 2] Acrylic copolymer solutions used in Examples 2 to 7 and Comparative Examples 1 and 2 were obtained in the same manner as in the acrylic copolymer solution 1 used in Example 1 above, except that the monomer compositions were as shown in Table 1.
[0029] <Production of Pressure-Sensitive Adhesive Composition and Surface Protective Film> [Example 1] To the acrylic copolymer solution 1 (100 parts by weight of the acrylic copolymer) produced as described above, 1.0 part by weight of 1-octylpyridinium pentafluorobenzenecarboxylate and 1.5 parts by weight of Coronate HX (an isocyanurate of a hexamethylene diisocyanate (HDI) compound) were added and mixed by stirring to obtain an adhesive composition of Example 1. This adhesive composition was applied onto a release film made of a silicone resin-coated polyethylene terephthalate (PET) film, and then dried at 90° C. to remove the solvent, thereby obtaining an adhesive sheet with an adhesive layer thickness of 25 μm. Thereafter, an adhesive sheet was transferred to the side opposite the antistatic and antifouling treated side of a polyethylene terephthalate (PET) film having one side treated with antistatic and antifouling treatment, thereby obtaining a surface protection film of Example 1 having a laminate structure of "antistatic and antifouling treated PET film / adhesive layer / release film (silicone resin coated PET film)". [Examples 2 to 7 and Comparative Examples 1 to 2] Surface protection films of Examples 2 to 7 and Comparative Examples 1 and 2 were obtained in the same manner as the surface protection film of Example 1 above, except that the compositions of the additives were as shown in Table 1.
[0030] In Table 1, the mixing ratio of each component is shown in parentheses in parts by weight, calculated with the total of alkyl acrylate monomers (when a copolymerizable vinyl monomer is used, the total of alkyl acrylate monomer and copolymerizable vinyl monomer) being 100 parts by weight. The compound names of the abbreviations of each component used in Table 1 are shown in Table 2. Coronate (registered trademark) HX, Coronate (registered trademark) HL, and Coronate (registered trademark) L-45 are trade names of Nippon Polyurethane Industry Co., Ltd., TETRAD (registered trademark)-X is a trade name of Mitsubishi Gas Chemical Company, Inc., and Duranate (registered trademark) 24A-100 is a trade name of Asahi Kasei Chemicals Corporation.
[0031] [Table 1]
[0032] [Table 2]
[0033] <Test methods and evaluation> The surface protection films in Examples 1 to 7 and Comparative Examples 1 and 2 were aged for 7 days under an atmosphere of 23°C and 50% RH, and then the release film (a silicone resin-coated PET film) was peeled off to expose the adhesive layer, which was used as a sample for measuring surface resistance value. Furthermore, this surface protection film with the adhesive layer exposed was attached to the surface of a polarizing plate attached to a liquid crystal cell via the adhesive layer, and after leaving it for one day, it was autoclaved at 50°C and 5 atmospheres for 20 minutes and then left at room temperature for a further 12 hours to prepare a sample for measuring adhesive strength.
[0034] <Adhesive strength> The measurement sample obtained above (a 25 mm wide surface protection film attached to the surface of a polarizing plate) was peeled off in the 180° direction at a low speed (0.3 m / min) using a tensile tester, and the peel strength was measured and taken as the adhesive strength.
[0035] <Surface resistance> After aging and before bonding to a polarizing plate, the release film (a silicone resin-coated PET film) was peeled off to expose the adhesive layer, and the surface resistance of the adhesive layer was measured using a resistivity meter, Hiresta UP-HT450 (manufactured by Mitsubishi Chemical Analytech).
[0036] The evaluation results are shown in Table 1. The surface resistance is expressed as "m×10 +n " is expressed as "mE+n" (where m is any real value and n is a positive integer).
[0037] The surface protection films of Examples 1 to 7 have a surface resistance of 1.0×10 +12 The adhesive strength was Ω / □ or less, and it had a suitable adhesive strength. In other words, it was possible to improve issues such as antistatic properties and reworkability. The surface protection films of Comparative Examples 1 and 2 have a surface resistance of 1.0×10 +12 The surface protective film of Comparative Example 1 had too strong an adhesive strength, and therefore had problems with reworkability.
Claims
[Claim 1] A pressure-sensitive adhesive film comprising a substrate and a pressure-sensitive adhesive layer formed on one side thereof, the pressure-sensitive adhesive layer being formed by crosslinking a pressure-sensitive adhesive composition containing an acrylic polymer, a crosslinking agent, and an antistatic agent, The acrylic polymer is a copolymer selected from the following acrylic polymers (1) to (3), Acrylic polymer (1): (A) a copolymer obtained by copolymerizing at least one (meth)acrylic acid ester monomer having an alkyl group with a carbon number of C1 to C14 and (B) at least one copolymerizable vinyl monomer containing a hydroxyl group and / or a carboxyl group; Acrylic polymer (2): (A) a copolymer obtained by copolymerizing at least two or more kinds of (meth)acrylic acid ester monomers having an alkyl group with a carbon number of C1 to C14, Acrylic polymer (3): (A) a copolymer obtained by copolymerizing at least one (meth)acrylic acid ester monomer having an alkyl group with a carbon number of C1 to C14 and at least one aromatic monomer; (A) the (meth)acrylic acid ester monomer having an alkyl group with a carbon number of C1 to C14 is at least one selected from the group consisting of methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, butyl (meth)acrylate, isobutyl (meth)acrylate, pentyl (meth)acrylate, hexyl (meth)acrylate, heptyl (meth)acrylate, octyl (meth)acrylate, isooctyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, nonyl (meth)acrylate, isononyl (meth)acrylate, decyl (meth)acrylate, cyclopentyl (meth)acrylate, and cyclohexyl (meth)acrylate; the hydroxyl group-containing copolymerizable vinyl monomer is at least one selected from the group consisting of 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 8-hydroxyoctyl (meth)acrylate, N-hydroxy(meth)acrylamide, N-hydroxymethyl (meth)acrylamide, and N-hydroxyethyl (meth)acrylamide; the pressure-sensitive adhesive composition contains, as the crosslinking agent, at least one kind selected from the group consisting of difunctional or higher isocyanate compounds, difunctional or higher epoxy compounds, difunctional or higher acrylate compounds, and metal chelate compounds; the pressure-sensitive adhesive composition contains, as the antistatic agent, an ionic compound in an amount of 0.1 to 10 parts by weight based on 100 parts by weight of the copolymer; The antistatic agent is a pentafluorophenyl group (C 6 F 5 group) and a cation, wherein the anion is 6 F 5 COO - , C 6 F 5 (CH 2 ) n COO - , C 6 F 5 (CF 2 ) n COO - , C 6 F 5 O (CH 2 ) n COO - , C 6 F 5 (CH=CH) n COO - , C 6 F 5 SO 3 - , C 6 F 5 (CH 2 ) n SO 3 - , C 6 F 5 (CF 2 ) n SO 3 - , C 6 F 5 O (CH 2 ) n SO 3 - , C 6 F 5 (CH=CH) n SO 3 - , C 6 F 5 O - , C 6 F 5 (CH 2 ) n O - , C 6 F 5 (CF 2 ) n O - , C 6 F 5 O (CH 2 ) n O - , (C 6 F 5 ) 2 CHO - , (C 6 F 5 ) 3 CO - , C 6 F 5 OSO 3 - , C 6 F 5 O (CH 2 ) n SO 3 - , C 6 F 5 O (CF 2 ) n SO 3 - , (C 6 F 5 CO) 2 N - , (C 6 F 5 CO) 3 C - , (C 6 F 5 SO 2 ) 2 N - , (C 6 F 5 SO 2 ) 3 C - , (C 6 F 5 OSO 2 ) 2 N - , (C 6 F 5 OSO 2 ) 3 C - , C 6 F 5 P.O. 3 2- The adhesive film is characterized in that the anion is one selected from the group consisting of:
Citation Information
Patent Citations
Insulating method and device for rotary electric machine
JP1982034754A
Pressure-sensitive adhesive
JP1988225677A
Manufacture of high manganese steel
JP1989092312A
Adhesive composition
JP1996199130A
Surface protective film for liquid crystal display panel
JP1999070629A